Local Wisdom in the Figurative Language of the Randai Tradition in Aneuk Jamee Weddings: An Anthropolinguistic Study - Wafa Dhina Aliyah; Yunisrina Qismullah Yusuf; Zulfadli A. Aziz (Masyarakat Linguistik Indonesia Universitas Andalas, 2025)
In oral cultures, language is considered a vital means of transmitting social norms, values, and local wisdom to the next generation. This study discusses the Randai tradition in wedding ceremonies in Aneuk Jamee, Aceh, Indonesia, and reflects on the role of figurative language in conveying local wisdom. Based on Minangkabau culture and its acculturation into Acehnese culture, Randai incorporates poetic language and proverbs, as well as symbols associated with artistic and moral values. The research employed an anthropological approach and was conducted in Ladang Village, South Aceh, Indonesia, using observation, audio recordings, and in-depth interviews with five elders in the community. The results revealed that the local wisdom embedded in the figurative language includes: harmony on ‘politeness and thoughtful speech’, and ‘social equality’, education on ‘responsibility and commitment’, and ‘obedience to custom and discipline’ (5 metaphors), cooperation on ‘gotong royong’ and ‘unity and mutual support’ (1 hyperbole), spirituality on ‘humility and modesty’ (1 litotes), and another in spirituality on ‘optimism and hope’ (1 paradox). This tradition not only reflects the shared values and cultural continuity but also functions as a living course, communicating ethics, emotional intelligence, and intergenerational respect. In a modern context, it strengthens group identity while encouraging younger generations to uphold ancestral wisdom. The use of such devices showed that Randai is not just a form of entertainment but also a medium of culture and education, strengthening the Aneuk Jamee community’s moral and Islamic values and identity, especially among the younger generation of Acehnese.